PENGARUH CAPITAL ADEQUACY RATIO (CAR), FINANCING TO DEPOSIT RATIO (FDR), NON PERFOMING FINANCING (NPF), BIAYA OPERASIONAL PENDAPATAN OPERASIONAL (BOPO) TERHADAP RETURN ON ASSET (ROA) PADA BANK UMUM SYARIAH TAHUN 2015-2018 - Rudi Ramadhani; Amelia Anwar; Eka Travilta Oktaria (Business and Enterpreneurship Journal (BEJ), 2021)
This study aims to determine the effect of knowing the effect of Capital Adequacy Ratio (CAR), Financing to Deposit Ratio (FDR), Non-Performing Financing (NPF), and Operational Expenditures on Operating Income (BOPO) on Return on Assets (ROA) at Banks Sharia General in 2015-2018. This study uses quantitative data with secondary data sources in the form of financial statements. The sampling technique used was purposive sampling and obtained a sample of 4 Islamic banks. Data taken from quarterly financial reports obtained from the official website of each bank is a research sample. The results of this study show that the results of the test simultaneously (Test F) obtained F count 73,367 f table 2,53 with a significant result of 0,000 0,05, which means that CAR, FDR, NPF and BOPO jointly influence and significant to ROA. While the test results t (1) CAR has a value of t count 2.195 t table 2.00172 with a significant level of 0.032 0.05, which means that CAR has a positive and significant effect on ROA. (2) FDR has a value of t count 2.333 t table 2.00172 with a significant level of 0.023 0.05, which means that FDR has a positive and significant effect on ROA. (3) NPF has a value of t count 1.437 t table 2.00172 with a significant level of 0.156 0.05, which means that NPF has no effect and is not significant towards ROA. (1) BOPO has a value of t count -14.915 t table 2.00172 with a significant level of 0,000 0.05 which means that BOPO has a negative effect and is significant for ROA.Keywords: CAR, FDR, NPF, BOPO and ROA